Integrable supersymmetric chain without particle conservation. (24th February 2016) - de Gier, Jan; Feher, Gyorgy Z; Nienhuis, Bernard; Rusaczonek, Magdalena
Abstract: We introduce a new integrable supersymmetric lattice chain which violates fermion conservation and exhibits fermion–hole symmetry. The model displays exponential degeneracy in every eigenstate including the ground state. This degeneracy is expressed in the possibility to create any number of zero modes reminiscent of Cooper pairs.